Comparison of the shear test results of a cable bolt on three laboratory test apparatuses. (January 2017) - Li, Xuwei; Aziz, Naj; Mirzaghorbanali, Ali; Nemcik, Jan
Highlights: Existing shear test apparatuses for assessing bolt shear performance are briefly reviewed. Key influencing factors to consider when designing a shear test apparatus are discussed. A comparative analysis has been conducted highlighting the differences between the single and double shear tests. Abstract: The shear performance of cable bolt is important in assessing its load transfer capacity for effective rock strata reinforcement, which has not yet been thoroughly investigated and understood. Tests carried out in laboratory to study the cable shear performance can be simply classified into two types, the Single Shear Test (SST) and the Double Shear Test (DST). A variety of single and double shear test apparatuses developed in the past were reviewed and the main controlling factors when designing a new shear test apparatus were concluded based on the existing shear test apparatuses and their application. Four cable bolts were tested in laboratory conditions using the DST apparatus developed in the University of Wollongong, the British Standard Single Shear Test apparatus (BSST) and the Megabolt Single Shear Test apparatus (MSST) to compare and assess these different shear test apparatuses. Test results showed that the MSST results were completely different from the BSST results but similar to the DST results. Cable bolts tested in BSST tended to fail at small shear force and shear displacement in the form of inclined shear failure surfaces, whilst cable bolts installed in MSST and DST both tended to fail at greater shear force and shear displacement in the form of tensile cone and cup with bending deformation. It is concluded that both single and double shear test methods can effectively assess cable bolt shear performance as long as suitable apparatus dimensions and boundary conditions are used.